1997
DOI: 10.1093/emboj/16.8.2086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sin- versions of histone H4 on yeast chromatin structure and function

Abstract: Previous studies have identified single amino acid changes within either histone H3 or H4 (Sin- versions) that allow transcription in the absence of the yeast SWI-SNF complex. The histone H4 mutants are competent for nucleosome assembly in vivo, and the residues that are altered appear to define a discrete domain on the surface of the histone octamer. We have analyzed the effects of the Sin- versions of histone H4 on transcription and chromatin structure in vivo. These histone H4 mutants cause an increased acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
67
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 47 publications
8
67
0
Order By: Relevance
“…Previous studies have suggested that residual levels of Pho4 are present in the nucleus in high P i (38)(39)(40), despite its predominant cytoplasmic localization under these conditions (25). The presence of marked targeted 5me C at PHO5, PHO8, and PHO84 provides direct evidence of a low level of Pho4 binding in the presence of P i .…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have suggested that residual levels of Pho4 are present in the nucleus in high P i (38)(39)(40), despite its predominant cytoplasmic localization under these conditions (25). The presence of marked targeted 5me C at PHO5, PHO8, and PHO84 provides direct evidence of a low level of Pho4 binding in the presence of P i .…”
Section: Discussionmentioning
confidence: 77%
“…However, when we examined GAL10-MEL1 expression in a yeast strain carrying the hhf2-13 mutation in histone H4, we did not see any increase in stimulation by GAL4-TBP (Ryan and Morse, unpublished). Thus, although this sin mutation alleviates the requirement for SWI-SNF for transcriptional activation of an HO-lacZ reporter gene (58,75) and increases accessibility of nucleosomal DNA to MNase and Escherichia coli Dam methyltransferase in yeast (75), it evidently does not sufficiently perturb the local chromatin structure of the GAL10 promoter to allow activation by GAL4-TBP. We also employed an altered GAL10-MEL1 reporter having a LexA binding site between the GAL4 binding sites and the TATA element to ask whether artificial depletion of histone H4 would allow activation by LexATBP.…”
Section: Discussionmentioning
confidence: 94%
“…Whereas the Val111 of H3T does not directly interact with H2A/H2B and DNA, a mutation at Arg116 (to His) close to Val111 reportedly destabilized the nucleosome (14,15). This H3-R116H mutation in Saccharomyces cerevisiae has been identified as a Sin mutation that alleviates the requirement for the nucleosome-remodeling factor, Swi/Snf, which activates transcription (14,16). A structural study revealed that the H3-Arg116 residue may not directly interact with the DNA backbone and H2A/H2B, but instead forms a salt bridge with H3-Asp123 (17).…”
Section: Discussionmentioning
confidence: 99%